Application of PE‐RADSeq to the study of genomic diversity and divergence of two Brazilian marmoset species (Callithrix jacchus and C. penicillata). Issue 2 (12th August 2016) - Malukiewicz, Joanna; Guschanski, Katerina; Grativol, Adriana D.; Oliveira, Maria Adélia B.; Ruiz‐Miranda, Carlos R.; Stone, Anne C.
Abstract : Callithrix jacchus and C. penicillata are among the smallest anthropoid primates, are highly specialized tree gougers, and largely occupy Brazil's most extreme, semi‐arid biomes. However, the underlying genomic factors that underpin the evolution of these species and their unique traits are under‐investigated. Additionally, exotic populations of these two species are widely established throughout Brazil and hybridize with threatened native congers. Thus, both genomic and conservation factors call for a better understanding of C. jacchus and C. penicillata evolution. Here, we applied PE‐RADseq to characterize genomic variation in these two species, using six C. jacchus and seven C. penicillata individuals. We identified an average of 7, 463 and 5, 180 SNPs/individual in C. penicillata and C. jacchus, respectively, and also found 1, 395 variable sites that were represented in both species. C. penicillata showed overall higher levels of genetic diversity than C. jacchus at the variable sites present in both species. Additionally, among these variable sites, 106 showed relative interspecific divergence levels that were significantly higher than the genome‐wide average. We further compared relative and absolute divergence for C. penicillata and C. jacchus between RAD loci associated with the 106 significantly diverged variable sites and all other RAD loci present in both species. The former RAD loci set showed significantly elevated relative and absolute divergence measures in comparison to the latter set. This convergence suggests that C. jacchus and C. penicillata may have diverged under a scenario of gene flow under secondary contact. Here, we demonstrate that RADseq is an efficient method to simultaneously discover and genotype a large number of markers and validate the utility of RADseq for examining Callithrix evolution.